2006
DOI: 10.1249/01.mss.0000235359.16685.a3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Classroom-Based Program on Physical Activity and On-Task Behavior

Abstract: A classroom-based physical activity program was effective for increasing daily in-school physical activity and improving on-task behavior during academic instruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

39
615
7
22

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 535 publications
(693 citation statements)
references
References 22 publications
39
615
7
22
Order By: Relevance
“…4 Also, there is evidence of aerobic fitness level moderating aspects of academic performance 5 and children exhibiting increased 'ontask' classroom behaviour after brief exercise interventions. 6 Increases in the amount of curriculum time devoted to physical activity have also been reported to result in either no change or an improvement in students' academic achievement, 7 suggesting that increased exercise capably counteracts the negative impact of reduced academic instruction time, perhaps through improving cognition.Given these findings, recent initiatives to encourage increased childhood physical activity 8 may have important implications for mental as well as physical health. In adults executive functions such as working memory, goal-oriented processing, and inhibition are particularly improved by exercise interventions.…”
mentioning
confidence: 99%
“…4 Also, there is evidence of aerobic fitness level moderating aspects of academic performance 5 and children exhibiting increased 'ontask' classroom behaviour after brief exercise interventions. 6 Increases in the amount of curriculum time devoted to physical activity have also been reported to result in either no change or an improvement in students' academic achievement, 7 suggesting that increased exercise capably counteracts the negative impact of reduced academic instruction time, perhaps through improving cognition.Given these findings, recent initiatives to encourage increased childhood physical activity 8 may have important implications for mental as well as physical health. In adults executive functions such as working memory, goal-oriented processing, and inhibition are particularly improved by exercise interventions.…”
mentioning
confidence: 99%
“…Secondly, no additional teachers' training in CBPA breaks or researchers were needed to facilitate the CBPA breaks. In contrast, other classroombased PA breaks are required in-service training for the teachers [22,23]. Finally, the interruption to the child's academic learning was minimal, only six minutes.…”
Section: Discussionmentioning
confidence: 99%
“…A handful studies have examined the impact of classroombased PA breaks on attention and concentration quantitatively and qualitatively [3,[19][20][21][22][23][24][25][26][27][28]. The studies have shown that the classroom-based PA can improve children's attention and concentration [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations